1984
DOI: 10.1017/s0022112084000100
|View full text |Cite
|
Sign up to set email alerts
|

The resonant interaction of disturbances at laminar-turbulent transition in a boundary layer

Abstract: The three-dimensional resonant interaction of a plane Tollmien-Schlichting wave, having a frequency f1, with a pair of oblique waves having frequencies ½ f1, was observed and studied experimentally. In the initial stages, the interaction proved to be a parametric resonance, resulting in the amplification of small random priming (background) oscillations of frequency ½ f1, and of a packet of low-frequency oscillations. The resonant interaction of waves in a boundary layer was investigated also by introducing a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
152
0
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 374 publications
(172 citation statements)
references
References 15 publications
17
152
0
1
Order By: Relevance
“…Indeed, we have confirmed that compressibility effects are negligible by examining the growth rate of the low-amplitude perturbations in the linear and weakly nonlinear regimes. In a recently published work involving the same dataset (Sayadi et al 2013 we found that the evolution of the perturbations in the early transitional regime agrees with the evolution of the perturbations in H-and K-type experiments (Kachanov & Levchenko 1984). In addition, the turbulence statistics in the fully turbulent section of the present simulation compare well with equivalent statistics taken from the incompressible DNS of Wu & Moin (2009).…”
Section: Computational Set-upsupporting
confidence: 82%
See 1 more Smart Citation
“…Indeed, we have confirmed that compressibility effects are negligible by examining the growth rate of the low-amplitude perturbations in the linear and weakly nonlinear regimes. In a recently published work involving the same dataset (Sayadi et al 2013 we found that the evolution of the perturbations in the early transitional regime agrees with the evolution of the perturbations in H-and K-type experiments (Kachanov & Levchenko 1984). In addition, the turbulence statistics in the fully turbulent section of the present simulation compare well with equivalent statistics taken from the incompressible DNS of Wu & Moin (2009).…”
Section: Computational Set-upsupporting
confidence: 82%
“…Both H-and K-type transitions are 280 T. Sayadi, P. J. Schmid, J. W. Nichols and P. Moin examples of transitions in which prescribed low-amplitude waves, confined near the wall, develop without external perturbations. Experiments by Schubauer & Skramstad (1947), Klebanoff, Tidstrom & Sargent (1962) and Kachanov & Levchenko (1984) demonstrated that the interaction of two-dimensional Tollmien-Schlichting (TS) waves with lower-amplitude oblique waves results in three-dimensionality in the flow. This interaction is well described by the linear Orr-Sommerfeld equation and precedes the development of Λ-vortices (Berlin, Wiegel & Henningson 1999;Bake, Fernholz & Kachanov 2000).…”
Section: Introductionmentioning
confidence: 99%
“…All the modes have the same constant downstream propagation velocity throughout the whole box. This wave synchronism condition, which should be satis ed in order to have resonant w a v e i n teractions between all these modes, was observed in the experiments of Corke andMangano 1989 andKachanov andLevchenko 1984 . Wall-normal distributions of amplitude and phase of the fundamental and subharmonic modes for the velocity u are shown in Fig. 4.…”
Section: Linear and Weakly Nonlinear Stagesmentioning
confidence: 71%
“…Figure 3 shows the streamwise evolution of amplitude and phase of several harmonics for the streamwise velocity u, compared with the experiment b y Kachanov and Levchenko 1984 , where the Reynolds number is de ned as Re x = xU 1 = and x is the distance from the leading edge of the plate. Goodoverall agreement is obtained between the numerical simulation and the experiment.…”
Section: Linear and Weakly Nonlinear Stagesmentioning
confidence: 99%
“…Experimentally, Kachanov & Levchenko (1984) and Borodulin, Kachanov & Koptsev (2002) discussed the influence of the initial phase shift between the fundamental wave and the sub-harmonic pair on the resonant amplification. The phase shift has particular importance for the H-type interaction.…”
mentioning
confidence: 99%